Helicobacter cinaedi bacterium association with atherosclerosis and other diseases - Voronina, Alice K.; Arapidi, Georgij P. (Frontiers in Microbiology, 2024)
Helicobacter is a genus of spiral-shaped Gram-negative enterohepatic bacteria whose members are capable of causing bacteremia in humans. One of the poorly studied members of this genus is the bacterium Helicobacter cinaedi.This microorganism was first isolated from human fecal samples in 1984. Although it was long considered to be associated with only immunocompromised patients, more evidence in recent years has implicated H. cinaedi in causing serious pathologies in immunocompetent populations. In addition, H. cinaedi is also reported to be associated with a few chronic or severe illnesses, such as atherosclerosis, which in turn can lead to the development of other cardiovascular pathologies: one of the leading causes of mortality worldwide. H. cinaedi often goes unnoticed in standard diagnostic methods due to its slow growth under microaerobic conditions. This often leads to significant underdetection and hence undermines the role of this bacterium in the pathogenesis of various diseases and the extent of its spread in humans. In this review, we have compiled information on pathologies associated with H. cinaedi, the occurrence of the bacterium in humans and animals, and the latest developments in diagnosing the bacterium and treating associated diseases.